2021
DOI: 10.1038/s41586-020-03124-4
|View full text |Cite
|
Sign up to set email alerts
|

Functional refolding of the penetration protein on a non-enveloped virus

Abstract: Non-enveloped viruses must create a transient membrane lesion to initiate infection by transferring their genomes into a target cell 1 . Rotaviruses offer a particularly favorable opportunity to visualize the mechanism for subviral particle delivery, the principal function of their outer-layer protein, VP4 2 – 4 . We show here by electron cryomicroscopy (cryo-EM) that VP4, activated by cleavage to VP8* and VP5*, rearranges on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(97 citation statements)
references
References 52 publications
(69 reference statements)
1
84
0
Order By: Relevance
“…As illustrated in Figure 1 , during RV release, RV particles can be assembled in five steps., (i) RV particles relocate from the endoplasmic reticulum (ER) to the apical plasma membrane bypassing the Golgi complex; (ii) RV NSP4 protein halts the early secretory pathway and arrests normal ER-to-Golgi membrane trafficking; (iii) VP4 and VP7 are detected in a filamentous array; (iv) VP4 present at the plasma membrane associated with microtubules; and (v) interaction of NSP4 and lipid membranes mimicking endocytosis. Most recently, Herrmann and colleagues using electron cryomicroscopy demonstrated the involvement of VP4 gene in the initial RV penetration into the membranes of target cells ( 41 ). They showed that when VP4 is cleaved into VP5* and VP8*, it transitions from an upright to a reversed conformation leading to membrane perforation and virion attachment.…”
Section: Rotavirus Cell Entrymentioning
confidence: 99%
“…As illustrated in Figure 1 , during RV release, RV particles can be assembled in five steps., (i) RV particles relocate from the endoplasmic reticulum (ER) to the apical plasma membrane bypassing the Golgi complex; (ii) RV NSP4 protein halts the early secretory pathway and arrests normal ER-to-Golgi membrane trafficking; (iii) VP4 and VP7 are detected in a filamentous array; (iv) VP4 present at the plasma membrane associated with microtubules; and (v) interaction of NSP4 and lipid membranes mimicking endocytosis. Most recently, Herrmann and colleagues using electron cryomicroscopy demonstrated the involvement of VP4 gene in the initial RV penetration into the membranes of target cells ( 41 ). They showed that when VP4 is cleaved into VP5* and VP8*, it transitions from an upright to a reversed conformation leading to membrane perforation and virion attachment.…”
Section: Rotavirus Cell Entrymentioning
confidence: 99%
“…It is possible that reduced infectivity of VP4 mutants could be due to inefficient conformational transition of VP4 following proteolytic cleavage [1,23,87]. Following cell attachment, VP8* lectin domains at the tip of VP4 dissociate and expose the hydrophobic loops of the VP5* β-barrel domains [21,67,68]. This enables interaction of the VP5* hydrophobic loops with the lipid bilayer and perforation of the target membrane by the VP5* foot domain, leading to RV entry, analogous to refolding of influenza virus haemagglutinin during membrane fusion [67,68,[88][89][90][91][92][93].…”
Section: Discussionmentioning
confidence: 99%
“…Rice of BTV of dipteran cells and plant reoviruses of hemipteran cells (see sections 7 and 8). Regardless of whether core particles are double-or singlelayered, the outer capsid layers of orthoreoviruses, rotaviruses and BTV contain the host receptor-binding proteins and the machinery for the penetration of the cellular membrane for their efficient delivery in the cytoplasm during their infection of mammalian cells (Herrmann et al, 2021;Roth et al, 2021). During this process, the outer layer proteins are discarded in the endosomes or at the cell surface while the core particles enter the cytoplasm as intact entities that initiate transcription without further disassembly (Lourenco and Roy, 2011;Patel and Roy, 2014).…”
Section: Mammalianmentioning
confidence: 99%
“…In the processed spike protein VP4, the main function of VP8 ∗ consists of the attachment to the cell surface, while VP5 ∗ provides the means to perforate the cellular or vesicular membrane ( Herrmann et al, 2021 ). VP4 is a trimer but structurally rearranges on the surface of the virions in an asymmetric configuration that consists of foot, stalk, body and head regions ( Rodríguez et al, 2014 ).…”
Section: Molecular Mechanism Of Cellular Entry By Rotaviruses In Mammalian Cellsmentioning
confidence: 99%
See 1 more Smart Citation